ALAT PERAGA ELEKTRONIK BERBASIS ARDUINO DENGAN KELUARAN CAHAYA DAN SUARA UNTUK PENGENALAN WARNA BAGI BALITA - Rustamaji Rustamaji; Shieren Dikah Aprilia Sandakila; Kania Sawitri (Universitas Lampung, 2024)
Recognizing the color of an object is a basic thing that must be taught to toddlers. This research aims to design and realize a color recognition teaching aids for toddlers, designed using an electronic device based on an Arduino Uno microcontroller with output in the form of audio sound and light. This tool consists of: an object in the form of a colorful plastic ball, an input device in the form of a TCS230 color sensor, a processing and controlling device in the form of an Arduino Uno microcontroller, and output devices in the form of a DC servo motor, RGB LED strip, and loudspeaker. Based on the results of measurements and tests that have been carried out, the Arduino Uno microcontroller can function to control all input and output devices. The TCS230 color sensor successfully detected the color pixel value (RGB) of the object, and issued wavelength information in the form of frequency quantities. The DC servo motor can move to direct the object to the mouth of the slide pipe. The loudspeaker can produce audio sounds according to the name of the object's color. RGB LED strips can emit light according to the color of the object. Overall, the results of the design and realization, measurement and testing of color recognition teaching aids for toddlers are in accordance with what was planned.